Cellular Solutions: Evaluating Single-Cell Proteins as Sustainable Feed Alternatives in Aquaculture - Korale Kankanamge Dinuka Chamodi; Nguyen Thanh Vu; Jose A. Domingos; Jiun-Yan Loh (Biology, 2025)
The rapid expansion of the global population has intensified the demand for protein-rich food sources, positioning aquaculture as a crucial sector in the endeavor to alleviate global hunger through the provision of high-quality aquatic protein. Traditional protein sources such as fishmeal have historically served as the foundation of aquafeeds; however, their elevated costs and limited availability have catalyzed the search for sustainable alternatives. These alternatives encompass plant-based proteins, insect meals, and, more recently, single-cell proteins (SCPs), which are derived from microorganisms including bacteria, yeast, fungi, and microalgae. Nonetheless, SCP remains in its nascent stages and currently accounts for only a minor fraction of aquafeed formulations relative to other established alternatives. The production of SCP utilizes low-cost substrates, such as agricultural and dairy wastes, thereby supporting waste mitigation and principles of the circular economy. This review elucidates the nutritional value of SCPs, their potential for biofortification, and their emerging roles as functional feeds with immunomodulatory and nutrigenomic effects. Additionally, the review underscores the potential of endophytes as a novel SCP source, highlighting their underutilized capacity to foster sustainable innovations in aquafeeds.